Blockchain-Based Connectivity Provisioning in Multiple Transport SDN Domains - Alemany, Pol; Vilalta, Ricard; Munoz, Raul; Casellas, Ramon; Martinez, Ricardo (2021 International Conference on Optical Network Design and Modeling (ONDM), 2021)
Hierarchical Software Define Networking (SDN) architectures is used to manage the co-existence of multiple domains by having an element on top. A collaborative relation-ship between domains, might solve this issue. Blockchain may become the key element for this change to happen. This paper presents a Blockchain-based architecture to provide SDN actions to configure connectivity services in transport domains. The results presented show that the use of Blockchain is a promising candidate for inter-domain SDN control.